Comparative Study of Automated Testing Tools: Selenium and Quick Test Professional (International Journal of Engineering and Computer Science, 2014)
Software testing is one of the most important phase of software development. Automated testing is an effective testing process that reduces the effort of manual testing. But it is important to select a best suitable tool for testing. The main objective of the paper is to conduct a comparative study of automated tools such as Selenium and Quick test professional (QTP). The main objective of this paper is to evaluate and compare the automated software testing tools to determine their usability, maintenance and effectiveness. There is wide variety of software testing tool in the market with features like web Testing, Window application, etc.